Facilitators and barriers to COVID-19 vaccination among incarcerated people and staff in three large, state prisons: a cross-sectional study - Ingie Osman; Antonio Williams; Katie Pierson; Eric Ryu; Rebecca J. Shlafer (BMC, 2023)
Abstract Background The COVID-19 pandemic has disproportionately impacted individuals in carceral facilities - both incarcerated people and staff. Vaccination is an important tool in reducing the risk of COVID-19 infection, hospitalization, and death. While the importance of promoting vaccination is clear, there are considerable barriers to doing so. This study aims to better understand: (1) why individuals chose to receive the COVID-19 vaccine; (2) why individuals were hesitant to vaccinate; (3) what motivators might influence a person's decision to get vaccinated; and (4) what sources of information about COVID-19 vaccination people trust. Methods We conducted a survey of incarcerated people and facility staff in three, large state prisons in Minnesota to identify barriers and facilitators to COVID-19 vaccination. Facilities were recruited to participate through purposive sampling, and surveys were administered between November and December 2021. Descriptive statistics were calculated using Stata. Results Findings demonstrate that, for incarcerated individuals (N = 1,392), the most common reason for getting vaccinated was to return to normal activities in prison (61%, n = 801); the most common reason for being hesitant to get vaccinated was "other" (41%, n = 342), with individuals citing a variety of concerns. For staff (N = 190), the most common reason for getting vaccinated was to protect the health of family and friends (79%, n = 114); the most common reasons for being hesitant were disbelief that vaccination is necessary (55%, n = 23) and distrust of healthcare and public health systems (55%, n = 23). Incarcerated individuals reported that monetary and programmatic incentives would help motivate them to get vaccinated, while staff members said speaking with healthcare professionals and monetary incentives would help motivate them. Lastly, trusted sources of information for incarcerated individuals were healthcare professionals outside of prisons and jails, along with friends and family members. Staff members reported that they trusted healthcare professionals and national health organizations for information about COVID-19 vaccination. Conclusions While considerable barriers to COVID-19 vaccination persist among both incarcerated individuals and staff members, these findings also highlight areas of intervention to increase COVID-19 vaccine confidence and promote health equity among those disproportionately impacted by the COVID-19 pandemic.